An internship report and comparative study of educational psychologists' consultation practices in St. John's, Newfoundland and Harlow, West Essex - Mercer, Christopher Bruce, 1968- (1995)
Thesis (M.Ed.)--Memorial University of Newfoundland. Education Bibliography: leaves 68-71. In process